KONSEP PENGEMBANGAN KAWASAN AGROWISATA BERBASIS TANAMAN HORTIKULTURA - Gunarto, Anton (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2009)
Agrotourism is an alternative form of tourism which makes use agro activities as the main attraction. In addition to recreation, agrotourism also provides educational activities in the area of farming. The main attraction of agrotourism is the beauty of nature and the commodity special to the agrotourism area or site. Agrotourism development is based on co, conservation ( conservation-based tourism) and community (community-based tourism). This article analyzes the concepts of agrotourism development based on horticulture.